The characteristics of Great Cultural Projects and their impact on architectural and urban heritage (1850–2012) - Biedermann, Anna Maria; Januchta-Szostak, Anna (Arte, Individuo y Sociedad, 2021)
This study examines Great Cultural Projects (GCPs) as an element of the developmental process of cities. For this study, GCPs are regarded as a global phenomenon rather than cases that must be analyzed independently. The study focused on four types of GCPs: world and international exhibitions, horticultural exhibitions, Olympic Games, and the European Capitals of Culture. The research sample comprised 183 GCPs globally, organized between the middle of the 19th century to the beginning of the 21st century. The study analyzed the influence of different GCPs on city structure and urban heritage and focused on the distinctive development of each GCP type. The study’s novelty lies in recognition of the four main types of GCPs’ potential for multidimensional urban development and their diversified impact on the transformation of modern cities, along with the identification of potential threats, benefits, and development opportunities related to different GCP types.